Hexosamine Biosynthetic Pathway and Glycosylation Regulate Cell Migration in Melanoma Cells - de Queiroz, Rafaela Muniz; Oliveira, Isadora Araújo; Piva, Bruno; Bouchuid Catão, Felipe; da Costa Rodrigues, Bruno; da Costa Pascoal, Adriana; Diaz, Bruno Lourenço; Todeschini, Adriane Regina; Caarls, Michelle Botelho; Dias, Wagner Barbosa (Frontiers in Oncology, 2019)
The Hexosamine Biosynthetic Pathway (HBP) is a branch of glycolysis responsible for the production of a key substrate for protein glycosylation, UDP-GlcNAc. Cancer cells present altered glucose metabolism and aberrant glycosylation, pointing to alterations on HBP. Recently it was demonstrated that HBP influences many aspects of tumor biology, including the development of metastasis. In this work we characterize HBP in melanoma cells and analyze its importance to cellular processes related to the metastatic phenotype. We demonstrate that metastatic melanoma cells present decreased HBP flux compared to primary tumor-derived cells and this is followed by decreased glycosylation of intracellular proteins with limited effect on extracellular glycosylation. An increase in HBP flux, as well as increased O-GlcNAcylation, leads to decreased cell motility and migration. High HBP flux, but not hyper-O-GlcNAcylation, decreases the activity of metalloproteases 2 and 9. Our data demonstrates that HBP is altered in metastatic melanoma cells and its modulation influences important aspects for metastasis by at least two independent mechanisms.